(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The purpose of this study is to investigate and analyse the determinants of customer loyalty towards Reliance Jio – a major Indian telecommunication service provider. It can be unquestionably said that loyal customers are very crucial for a company’s success and have a positive impact on its profitability. However, retaining customers might be trickier and more difficult than it seems. To determine the crucial factors that have a significant impact on customer loyalty 176 Jio customers in India were surveyed, who were availing or had previously availed the telecom operator’s services. Findings of the study showed that out of the 10 determinants considered for the study, only 4 determinants had a significant impact on customer loyalty. They were Brand experience, Corporate image, Switching cost and Satisfaction. It also suggested that the most dominant factor among them is Jio’s Brand experience. The findings suggest Telecom operators like Jio to emphasize more on improving their brand experience and corporate image which have high weightage in developing customer loyalty. This study can act as a model for researchers and marketers to get a much better understanding of the unpredictable customer behaviour and their decision making while making purchases.